Спасательные раскопки кургана на р. Красная - Красильников, К.И.; Красильникова, Л.И.; Пробейголова, А.С. (Археологічні дослідження в Україні, 2009)
The barrow 2 belongs to the burial ground II on the Krasna River where the rescue excavations were conducted. 4 tombs of Catacomb culture period were discovered under the partly preserved mound. The inventory included ceramic (dishes and a jug) and wooden pottery, bone and metal objects, beads, and alabaster bowl. The burials correspond to the period of High Bronze Age from the end of the 3rd to the beginning of the 2nd millennium BC.